Early Detection to Determine the Health Status of RW 09 Community in Margahayu Utara Village, Bandung City - Fuadah, Fahmi; Sianipar, Imelda; Siagian, Ira Ocktavia; Irawan, Galuh Chandra; Maryani, Lidya; Sinaga, Anni; Tresnajaya, Reynaldi (CV Media Inti Teknologi, 2023)
The pandemic of the Covid-19 Virus in the past few years has become a major global problem, because everyone can be infected with the virus. is a major problem in the world, because everyone can be infected with the Corona Virus. covid also affects Non-Early Diseases. This community service aims to provide early detection training to determine the health status of the RW 09 community of North Margahayu Village, Bandung City. The materials provided include health related to pulmonary TB, stress management in women, handling stunting in children, and detecting and preventing breast cancer. This community service activity is carried out through a planning, implementation and evaluation process. With direct implementation in the field in the form of knowledge improvement education activities on September 14 and September 29. Data collection techniques using documentation. The community service carried out went well. It can be seen from the enthusiasm of cadres, mothers and children during the activity.